Voluntary and Involuntary Attention Affect Face Discrimination Differently - Esterman, Michael (2007)
Do voluntary (endogenous) and involuntary (exogenous) attention have the same perceptual consequences? Here we used fMRI to examine activity in the fusiform face area (FFA-a region in ventral visual cortex responsive to faces) and frontal-parietal areas (dorsal regions involved in spatial attention) under voluntary and involuntary spatial cueing conditions. The trial and stimulus parameters were identical for both cueing conditions. However, the cue predicted the location of an upcoming target face in the voluntary condition but was nonpredictive in the involuntary condition. The predictable cue-condition led to increased activity in the FFA compared to the nonpredictable cue-condition. These results show that voluntary attention leads to more activity in areas of the brain associated with face processing than involuntary attention, and they are consistent with differential behavioral effects of attention on recognition-related processes.